The multi-physics coupling method for parameter analysis in a high length-to-diameter ratio combustion system - Xinggan Lu; Shenshen Cheng; Kun Jiang (Case Studies in Thermal Engineering)
Based on cooperative deployment technology between drone swarms and dispersal systems, we have designed a gas generation and distribution system with a high length-to-diameter ratio to satisfy the requirements for both low overload and high thrust. A mathematical model and a computing framework coupling flow, structural, and thermal fields are established. Validation experiments and numerical simulations are subsequently carried out. The results indicate that the coupling framework accurately describes the energetic material combustion and flow in complex structures, thereby providing transient heat transfer boundary conditions and quantitatively compute thermal loss. Notably, axial pressure gradients and pressure fluctuations induced by a high length-to-diameter ratio predominantly occur prior to axial motion, while the influence of multi-physical field coupling effects becomes more pronounced following both the motion of the moving body and the boundary. Compared to a single physical field model, the coupling framework enhances the solution accuracy of the mass flow rate by 9.6 %∼13.8 %. And the accuracy improves by 6.7 % relative to the classic correction method and 31.9 % relative to the case without thermal loss. Moreover, the work performed by the gas accounts for 8.6 % of the total chemical energy, as limited by axial motion and the energy absorber. Thermal loss increases over time, reaching 17.5 % at 10 ms.